Determinan Audit Delay Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2023: Indonesia - Piona Piona; Halim Usman; Andika Rusli (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This study aims to analyze the influence of company size, profitability, leverage, and Public Accounting Firm (KAP) size on audit delay in mining companies listed on the Indonesia Stock Exchange (IDX). The population of this study was all mining sector companies listed on the IDX during a certain observation period. The sampling technique used a purposive sumpling method with the criteria of companies that published complete and consistent audited financial statements during the study period. The data analysis method used was panel data regression analysis with the help of Eviews software, through the stages of model selection testing, classical assumption testing, and hypothesis testing. The result of the study indicate that company size and KAP size have a negative effect on audit delay, while profitability and leverage have a positive effect on audit delay. This study provides practical implications for company management in improving the timeliness of financial reporting and for investors as a consideration in making investment decisions.